2014
DOI: 10.12688/f1000research.4563.2
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ENTPD3 does not impair nucleotide hydrolysis in primary somatosensory neurons or spinal cord

Abstract: Ectonucleotidases are membrane-bound or secreted proteins that hydrolyze extracellular nucleotides.  Recently, we identified three ectonucleotidases that hydrolyze extracellular adenosine 5’-monophosphate (AMP) to adenosine in primary somatosensory neurons.  Currently, it is unclear which ectonucleotidases hydrolyze ATP and ADP in these neurons.  Ectonucleoside triphosphate diphosphohydrolases (ENTPDs) comprise a class of enzymes that dephosphorylate extracellular ATP and ADP.  Here, we found that ENTPD3 (also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…In this study, we extended this work to demonstrate that NTPDase3 is expressed in trigeminal ganglia nociceptive neurons and their axons. These results are consistent with NTPDase3 being detected in primary nociceptive neurons in the dorsal root ganglia [ 11 , 27 , 28 ] and trigeminal peripheral nerve Raschkow’s plexus in dental pulp [ 18 ]. We further confirmed functional ecto-ATPase activity in trigeminal ganglia neurons and associated nerve fibers that project to the brainstem and inhibition by anti-NTPDase3 serum.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we extended this work to demonstrate that NTPDase3 is expressed in trigeminal ganglia nociceptive neurons and their axons. These results are consistent with NTPDase3 being detected in primary nociceptive neurons in the dorsal root ganglia [ 11 , 27 , 28 ] and trigeminal peripheral nerve Raschkow’s plexus in dental pulp [ 18 ]. We further confirmed functional ecto-ATPase activity in trigeminal ganglia neurons and associated nerve fibers that project to the brainstem and inhibition by anti-NTPDase3 serum.…”
Section: Discussionsupporting
confidence: 85%
“…By controlling the degradation of ATP within the synapse, NTPDase3 in presynaptic terminals is expected to reduce the amplitude and duration of pain signal transmission. However, NTPDase3 knock out mice display normal ecto-ATPase activity in the nociceptive lamina and do not show altered nociceptive behavior [ 27 ], suggesting that expression of alternative ecto-ATPases may be present or upregulated to compensate for the absence of NTPDase3 in the knock out mice. Interestingly, our ecto-ATPase activity blocking experiment showed that incubation with anti-NTPDase3 serum only partially reduced the ecto-ATPase activity in the nociceptive lamina.…”
Section: Discussionmentioning
confidence: 99%
“…The study proved its fundamental role in hemostasis and thrombosis. This was followed by the deletion of Entpd2 , the gene encoding NTPDase2, which allowed to analyze the function of the enzyme in taste buds [ 49 ], followed by the deletion of NTPDas3 [ 50 ]. Moreover, transgenic overexpression of NTPDase1 in mice or pigs permitted insight into its role in multiple organ systems.…”
Section: Nucleoside Triphosphate Diphosphohydrolasesmentioning
confidence: 99%